Correction: Conversion of monoculture cropland and open grassland to agroforestry alters the abundance of soil bacteria, fungi and soil-N-cycling genes. - PLOS ONE Staff (PLoS ONE, 2019)
[This corrects the article DOI: 10.1371/journal.pone.0218779.].